A Comparative Cross-sectional Study to Assess Knowledge Regarding Human Rights of Mentally Ill between Patient with Severe Mental Illness and People Without Mental Illness - Rashmi Rawat; Sudha Mishra; Adarsh Tripathi; Shweta Pandey (Annals of Indian Psychiatry)
Background: Human rights violation of mental illness (MI) in society by people without MI (PWMI) has been a common occurrence. The present study aims to compare the knowledge regarding the human rights of the mentally ill between asymptomatic patients with severe MI (SMI) and PWMI. Materials and Methods: A cross-sectional comparative design was adopted to study the knowledge regarding the human rights of MI among selected asymptomatic patients with SMI and people with PWMI (n = 122). Purposive sampling technique was used to collect the data through face-to-face interview using a structured questionnaire. Descriptive and inferential statistics were used to analyze the data. Results: In the present study, findings revealed that mentally ill patients are still struggling for their rights to be accepted as a part of society. MI patients are being discriminated against by the community because of their MI without getting equal treatment even after their recovery is accepted by both SMI and PWMI. SMI patients did not find the community a safe place contrary to PWMI. PWMI was aware of the rights and policies against harassment of mentally ill other than SMI patients. Conclusion: The study finds that the mentally ill patients are discriminated on various aspects and are not fully aware of their rights which conclude that community needs to be educated regarding the human rights of mentally ill to protect and promote the rights of PWMI.